Commercial banks listed on the Ho Chi Minh City stock exchange: An analysis of diversification, human capital, and performance - Nguyen, Kim Phuoc; Phan, Ngoc Thuy Nhu; Tran, Thi Tuong Van (Journal of Finance - Marketing Research, 2023)
Both portfolio diversification and the resource-based view theories advocate for firms to engage in the diversification of their activities to mitigate risks and enhance operational efficiency. Nevertheless, the subject at hand is a matter of contention due to the existence of a perspective that advocates for the superiority of specialization over diversification. The objective of this study is to determine the relationship between income diversification, human capital, and the financial performance of Vietnamese commercial banks. Based on an analysis of data obtained from 15 commercial banks listed on the Ho Chi Minh Stock Exchange from 2013 to 2022. Panel data regression method is used. The results indicate that diversification does not exert a significant influence on the performance of banks. However, it is seen that human capital positively impacts bank performance, suggesting a favorable relationship between human capital and bank performance. According to this result, income diversification has not had an impact on the efficiency of Vietnamese commercial banks. On the contrary, human capital is a factor that positively and strongly affects the performance of Vietnamese commercial banks. The findings of this study indicate that some management implications may be considered to enhance the operational efficiency of Vietnamese commercial banks.